Uma proposta de procedimento estruturado para implementação de SGI sistema de gestão integrado - Silva, Marcelo Estevam da (2013)
In this highly globalized and competitive world, one of the requirements of the organizational environment refers to the implementation of standardized management systems, which focus on improving relationships with its stakeholders. In this context, integrated management systems (IMS) arise, which coordinate the systems adopted by the organization in order to generate improvement of their efficiency and effectiveness. Several researchers and empirical studies have templates to facilitate the integration of management systems; however they do not detail how this process happens in organizations. Thus, this the main objective research´s is the proposes a structured procedure for implementation of IMS on small and medium-sized companies, using the method of multiple case studies. The analysis was conducted from the survey data and information in five companies with their IMS implemented or under implementation, considering the benefits, difficulties and process integration and management structure of the IMS. As the scope for this research, it´s chose to study how the integration of management systems ISO 9001, ISO 14001 and OHSAS 18001 occurs. With the results of this research, there were many similarities in the integration of management systems, steps for implementation of the IMS and the characteristics of the documentation developed. It was also identified difficulties and opportunities in the implementation of IMS in small and mid-sized businesses. Finally, it´s possible to propose a structured procedure to the implementation of an IMS on small businesses considering their processes, limitations and specific characteristics.